On the Products of k-Fibonacci Numbers and k-Lucas Numbers - Bijendra Singh; Kiran Sisodiya; Farooq Ahmad (International Journal of Mathematics and Mathematical Sciences)
In this paper we investigate some products of k-Fibonacci and k-Lucas numbers. We also present some generalized identities on the products of k-Fibonacci and k-Lucas numbers to establish connection formulas between them with the help of Binet's formula.